Tick Ectoparasites of Animals in Borderline of Iran-Iraq and Their Role on Disease Transmission - Omid Banafshi; Ahmad Ali Hanafi-Bojd; Mohamad Karimi; Faezeh Faghihi; Mojtaba Beik-Mohammadi; Sahere Gholami; Siavash Javaherizadeh; Hamideh Edalat; Hassan Vatandoost; Zakkyeh Telmadarraiy (Tehran University of Medical Sciences, 2018)
Background: Since ticks are potent vectors of various diseases, identification of these species are clinically important to protect the public health and control veterinary problems in the communities. We aimed to figure out the frequency of ticks on cows, goats, sheep, lambs, turtles and also obscure hosts in Kurdistan Province, bordered with Iraq June 2012 to May 2013. Methods: The hosts were selected randomly and examined individually for tick infestation. In case of infestation, ticks were collected using forceps and then preserved in 70% ethyl alcohol. All collected specimens were preserved in tubes and relative information was recorded and then identified based on morphological characteristics. Results: Totally, 1209 ticks were collected. The prevalence of ticks on cows, sheep, goats, lambs, turtles, poultry and obscure hosts was 11.33%, 55.41%, 6.53%, 5.95%, 0.9%, 8.02% and 11.82% respectively. The mean number of ticks on each animal was 1.6. Number of 5 genera, including Rhipicephalus, Argas, Ornithodoros, Hyalomma and Haemaphysalis and 9 species; including R. sanguineus (60.05%), R. bursa (0.08), Hy. anatolicum (12.33), Hy. asiaticum (1.49), Hy. aegyptium (0.91), Hy. marginatum (0.08), Haemaphysalis parva (4.22), Hyalomma sp. (0.99), Ornithodoros lahorensis (11.83), and Argas persicus (8.02) were identified. Conclusion: The most abundant species in this study area was Rh. sanguineus (60.05%). Due to high prevalence of tick specimens and a variety of collected species from sheep (55.41%), the vaccination of sheep and control of tick vectors are recommended.